From sea to cure: Discovery of marine-derived therapeutics against Fusarium solani in shrimps for enhancing aquaculture sustainability - Siam, Abdullah Al; Paul, Avijit Kumer; Joyoti, Shanjida Akter; Hossain, Md. Ifteker; Siddiquee, Noimul Hasan; Zaker, Bushra Binte; Farabi, Al-; Paul, Shyamal Kumar (PLOS ONE, 2025)
Fusarium solani, an Ascomycota filamentous fungus species, causes shell disease or mycotic infections in wild and farmed shrimps. It causes black gill disease in shrimps, which has no specific treatments, so cutting-edge pharmaceutical research to prevent glutamine synthetase is needed to stop it and reduce its negative effects on aquaculture productivity and health. In silico drug design has been evaluated as an innovative treatment for black gill disease in shrimps caused by F. solani. Initially, molecular docking targeted the Glutamine synthetase (AF-Q9UUN6-F1-v4), utilising a set of 1,191 seaweed metabolites found in the Seaweed metabolite database (SWMD). The three lead compounds, CID: 359 (Phloroglucinol), 11640528 ((6E,10E,14E)-16-(2,5-dihydroxy-3-methylphenyl)-2-hydroxy-2,6,10,14-tetramethyl hexadeca-6,10,14-trien-3-one), and 8768 (Protocatechualdehyde), have binding affinities of −5.752, −5.374, and −5.102 kcal/mol, with negative binding free energies of −16.27, −48.99, and −27.48 kcal/mol, respectively. Additionally, they have excellent ADMET properties, making them safe and effective, whereas HOMO-LUMO and QSAR studies suggest thermodynamic stability and biological activity, notably antifungal efficacy. The compounds were subsequently assessed to verify their durability and binding affinity to the target protein by conducting an MD simulation analysis. In the MD simulation, the ligands evaluated in this study exhibited notable robustness of the proteins’ binding site when complexed with CID: 8768, which suggests a strong interaction between the target and lead compound. Consequently, the compound obtained from the seaweed Polysiphonia lanosa may inhibit the fungal activity of F. solani glutamine synthetase protein, revealing that the compound might be an effective novel therapeutic candidate.